CONVECTIVE FLOW PAST AN INCLINED NON-UNIFORM SURFACE IN A SPARSELY PACKED POROUS MEDIUM - Mallikarjunaa, B (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
A mathematical model on Double diffusive MHD convective flow of a viscous fluid from an inclined wavy surface in a sparsely packed porous medium is developed. The governing equations for the conservation of mass, momentum, energy and concentration are non-dimensionalised and converted into boundary layer equations using similarity transformation and then solved using numerical technique. The computational results are carried out and presented graphically for the rate of heat and mass transfer for different values of the physical parameters, magnetic parameter, inclined parameter, ratio of conductivities, wavy amplitude parameter and porosity at the surface in two different cases, uniform permeability and variable permeability. This type of study find applications in petroleum geology, pharmaceutics, ceramics, manufacturing etc.